Effects of ultrasonication on electrical and self-sensing properties for fiber-reinforced cementitious composites containing MWCNTs - Jin-Seok Woo; Ai-Hua Jin; Hyun-Do Yun; Junhee Yu; Je Hyun Bae; Sun-Woo Kim; Soo-Yeon Seo; Gun-Cheol Lee; Seongwon Hong; Kang-Soo Kim; Sangyoung Han (Journal of Materials Research and Technology)
The uniform dispersion of carbon nanotubes (CNTs) is essential for enhancing the mechanical and electrical properties of cement composites. This improvement significantly increases their potential for use in embedded self-sensing applications within structural health monitoring (SHM) systems, which are defined as systems for monitoring, assessing, and evaluating structural conditions. To take advantage of this benefit, multi-walled carbon nanotubes (MWCNTs) were incorporated into fiber-reinforced cementitious composites, and the optimal method for achieving uniform dispersion was investigated by applying a specific ultrasonic dispersion energy level. The results revealed that the E500-CFRC specimen, treated with an ultrasonic energy of 500 J, achieved proper dispersion of MWCNTs, as evidenced by SEM images. This uniform dispersion significantly improved its mechanical strengths compared to other specimens. Additionally, this optimal dispersion within the cementitious composite enhanced self-sensing capability, accuracy to strain changes, and repeatability, indicating strong self-sensing capabilities. These results were validated by the strongest linear correlation observed between fractional change in resistance and compressive strain, with an R2 value of 0.935, outperforming other specimens. Furthermore, the proposed method enables well-dispersed MWCNTs to be integrated into a pre-mixed cementitious composite using the standardized mixing method, making it adaptable to a variety of cementitious mixtures. Given the limited research on the self-SHM performance of MWCNTs-filled cementitious composites under varying ultrasonic dispersion energy levels, this study contributes significantly to advancing the self-monitoring capabilities of reinforced concrete structures.